Pengaruh Model Project Based Learning terhadap Hasil Belajar Siswa Mata Pelajaran Teknologi Pengelasan Logam di SMK Negeri 2 Painan - Firman Saputra; Ambiyar Ambiyar (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
The subject of Metal Welding Technology is one of the compulsory subjects in the Fabrication major. However, many students' learning outcomes remain below the assessment criteria. This is suspected to be due to the use of conventional or less varied teaching methods, which result in limited student understanding and practical skills. Therefore, the researcher applied the Project-Based Learning (PjBL) model in this study, which aimed to determine its effect on students' comprehension. The type of research used was a quasi-experimental design with a post-test only control group, involving two classes: an experimental class and a control class. The study involved 16 students in each class. Data were collected through a test. Based on the data obtained, there was a difference between the experimental and control classes. This was proven by the average post-test scores of the experimental class, which was 80.62, compared to the control class, which was 65. These results indicate that the experimental class scored higher than the control class. The final data analysis included tests for normality, homogeneity, and hypothesis testing using a t-test. The results showed a significant (2-tailed) value of 0.001 for the comprehension group, which is less than 0.05. This means that the use of the Project-Based Learning model had a significant effect on students’ understanding and can be classified as effective, as it improved their comprehension.